Avaliação comparativa em educação e música entre crianças precoces com comportamento de superprodução e crianças com desenvolvimento típico - Koga, Fabiana Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this research was to identify the level of musical ability and differences in gifted for music, the students who attended the Students Care Program with Early Giftedness Behavior (PAPCS), of the Faculty of Philosophy and Science - UNESP, Marília in 2013. To achieve these goals it was necessary to create three groups G1, G2 and G3 matched for gender, age and school year. It is noteworthy that G1 was composed of participants from PAPCS, G2 consisted of children with no experience in music education and not early and/or gifted and G3 consisted of children with experience in music education and not early and/or gifted. Both G2 and G3 were as control groups to G1. For data collection were used specific instruments of music education area called Primary Measures of Music Audiation and Intermediate Measures of Music Audiation from Edwin Gordon and the Guiding record for observation of musical behavior of Violeta H. de Gainza. In addition to audio and video records which allowed the observation level of musical performance of the participants. To ensure greater scientific trustworthiness, the survey included the analysis of qualified judges of music and pedagogy area to select triggering activities that comprised the procedures of Gainza Record (1988). For the treatment of the data was necessary to use the Kruskal-wallis test, which allowed comparing groups and the Wilcoxon test, which allowed the intra-group analysis; also, through mediated distributions, we could analyze the specific performance of each of the three groups. As a parameter for the analysis of Guidance Record for the observation of music conduct of Gainza (1988), we used the National Curriculum Reference for Early Childhood Education and the National Curriculum Standards for Elementary Education, cycles I and II. After analyzing the data met F7 of G1, F5 of G3 and F14 of G2 that showed early musical giftedness and behavior to achieve the best results among all surveye

O intuito desta pesquisa foi identificar o nível de aptidão musical e as diferenças na superdotação para música, nos alunos que frequentaram o Programa de Atenção a Alunos Precoces com Comportamento de Superdotação (PAPCS), da Faculdade de Filosofia e Ciências - UNESP, Campus de Marília, em 2013. Para alcançar tais objetivos foi necessário a criação de três grupos G1, G2 e G3 pareados por gênero, ano escolar e idade. Ressalta-se que G1 foi composto por participantes do PAPCS, G2 foi composto por crianças sem experiência em Educação Musical e não precoces e/ou superdotadas e G3 foi composto por crianças com experiência em Educação Musical e não precoces e/ou superdotadas. Tanto G2 quanto G3 foram grupos de controle para G1. Para a coleta de dados foram utilizados instrumentos específicos da área da Educação Musical denominados Primary Measures of Music Audiation e Intermediate Measures of Music Audiation de Edwin Gordon e a Ficha orientadora para observação da conduta musical de Violeta H. de Gainza. Além de registros de áudio e vídeo os quais possibilitaram a observação de nível de desempenho musical dos participantes. Para garantir maior confiabilidade científica, a pesquisa contou com a análise de juízes qualificados da área de música e pedagogia para selecionar atividades disparadoras que compuseram os procedimentos da Ficha de Gainza (1988). Para o tratamento dos dados obtidos foi necessário a utilização do teste Kruskal-wallis, que permitiu compara os grupos e do teste Wilcoxon, que permitiu a análise intragrupo; também, por meio das distribuições de mediadas, foi possível analisar as especificidades do desempenho de cada um dos três grupos estudados. Como parâmetro, para a análise da Ficha Orientadora para a observação da conduta musical de Gainza (1988), utilizou-se o Referencial Curricular Nacional para a Educação Infantil e os Parâmetros Curriculares Nacionais...
Keywords: Educação especial; Crianças superdotadas; Musica - Instrução e estudo; Aptidão musical; Special education